Case Report: Potential Role of Corticosteroids in the Management of Post-COVID-19 Pneumonia - Aissaoui, Houari; Eskenazi, Anaïs; Suteau, Valentin; Adenis, Antoine; Drak Alsibai, Kinan (Frontiers in Medicine, 2021)
Certain patients who recover from severe pneumonia due to coronavirus 2019 (COVID19) remain symptomatic in the post-infectious period, either clinically, radiologically, or respiratory. The post-COVID19 period is characterized by clinical symptoms of varying duration from subject to another and seem not depends on the severity of initial pneumonia. The persisting of inflammatory and/or immune reactions in the post-COVID19 period may play a role in the development of pulmonary lesions. Here we report the case of a 61-year-old man with severe COVID19 pneumonia, complicated by acute respiratory distress syndrome and pulmonary embolism, which required the patient's admission to the intensive care unit and high-flow oxygen therapy. The patient was hospitalized for 23 days for the management of his severe COVID19 pneumonia. Afterwards, he was discharged home following a negative SARS-Cov-2 PCR test. The post-COVID19 period was characterized by a complex respiratory symptomatology associating cough, resting and exertional dyspnea requiring oxygen therapy for several weeks. Surprisingly, the follow-up chest CT scan performed four weeks after discharge revealed bilateral interstitial lung lesions. After ruling out pulmonary superinfection, the patient was treated with oral corticosteroid for three months at a digressive dose. In our case, the use of corticosteroid therapy in the post-COVID19 phase had improved the outcome of the lung disease. These benefits are characterized by a rapid symptomatic improvement, accelerated repair of pulmonary images, rapid oxygen withdrawal, and rapid return to daily activities.